Fiscal policy of Ukraine in conditions of decentralization: revenue of local budgets - Ostrovetskyy, V. (Економічний вісник Донбасу, 2017)
The article is considered the main trends of government decentralization process, as well as international experience and domestic practice of forming different level of budget revenues. Recommendations and proposals for improving the mechanism of formation of revenue of budgets of local governments, including by improving tax depreciation, taxation of individuals' income and consumption of excisable goods is suggested with account the needs of balanced interests of the state, local governments and taxpayers.